2014
DOI: 10.1002/eat.22273
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric alterations in the nucleus accumbens and caudate nucleus in bulimia nervosa: A structural magnetic resonance imaging study

Abstract: These findings suggest a contributory role of the caudate nucleus part of the dorsal striatum in the psychopathology of BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
(94 reference statements)
0
37
0
Order By: Relevance
“…26 Another study in BN suggested reduced caudate volume in the dorsal striatum but normal nucleus accumbens volume. 29 The studies in BN otherwise suggested normal or increased localized GM volume in orbitofrontal cortex and striatum. 8,27 A new study that investigated cortical thickness in BN found widespread brain surface volume reductions in frontal and temporo-parietal areas.…”
Section: Brain Volumementioning
confidence: 99%
“…26 Another study in BN suggested reduced caudate volume in the dorsal striatum but normal nucleus accumbens volume. 29 The studies in BN otherwise suggested normal or increased localized GM volume in orbitofrontal cortex and striatum. 8,27 A new study that investigated cortical thickness in BN found widespread brain surface volume reductions in frontal and temporo-parietal areas.…”
Section: Brain Volumementioning
confidence: 99%
“…AN and BN patients show reduced gray matter volume specifically in SN regions including the caudate nucleus, anterior cingulate cortex and insula, among other areas (Schäfer et al, 2010; Friederich et al, 2012; Frank et al, 2013; Coutinho et al, 2015). On DTI, AN patients show abnormal thalamic connectivity to the dlPFC and anterior PFC (Frieling et al, 2012; Hayes et al, 2015), and reduced fractional anisotrophy in the medial dorsal thalamic radiations (Biezonski et al, 2015; Hayes et al, 2015).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…For example, studies based on voxel-based morphometry (VBM) from MRI images have associated BN with increased grey matter volume (GMV) in the medial orbitalfrontal cortex and the ventral striatum [4], as well as in the insula [5], lingual gyri and inferior parietal lobule [6]. These and other studies also found reduced GMV in caudate and putamen [5,7], bilateral medial frontal, precentral gyri, right postcentral gyrus, left superior (SFG) and inferior frontal gyri [6]. Some brain structural studies have found cortical abnormalities in BN, such as reduced cortical thickness in the bilateral frontal, temporal and parietal lobes, negtively related to the severity of BN symptoms [8]; and reduced cortical thickness in the right pars triangularis, right superior parietal and left dorsal posterior cingulate cortices as well as greater cortical thickness in the left ventral posterior cingulate cortex [9].…”
Section: Introductionmentioning
confidence: 97%